PHARMACEUTICAL EVALUATION OF CHATURTHAMALAKA RASAYANA-AN AYURVEDA COMPOUND - Amit Ashok Gajarmal,; Gaurav, Sharma; Sudipt, Rath (International Journal of Ayurveda and Pharma Research, 2019)
In Ayurveda, Rasayana is mentioned as a unique preventive as well as curative therapy to achieve healthy long life. The modern medical world is seeking for an alternative class of immunomodulatory drugs, which is nothing but the category of Rasayana. Among this Rasayana formulation, Chaturthamalaka Rasayana (CR) is the one that formulation, mentioned just after Chyavanprasha Avaleha in classical literature of Charaka Samhita. CR consists of four formulations. It is nothing but the simple permutation and combination of Amalaki (Emblica officinalis Gaertn.), Bibhitaki (Terminalia bellerica Roxb.) and Haritaki (Terminalia chebula Retz.) collectively called as Triphala. In present study, it was prepared according to the classical standard operative procedure (SOP) so as to evaluate a physicochemical and phytochemical profile of CR as per standard lab protocols, for all the four formulations under CR, along with the main three raw drugs which ensure the quality. This pharmaceutical analysis differentiates one compound from another by developing its identification markers. As the CR has not been yet studied before, it will be more helpful to evaluate the pharmaceutical screening of this four formulations as an initial step towards standardization. In the future, this study will be helpful to prepare the monograph of CR in the Ayurvedic formulary of India (AFI).